Tafsir Pendidikan Islam dalam Tafsir Al-Burhan Karya Abdul Karim Amrullah (Analisis QS. Al-‘Alaq: 1-5) - Ahmad Murtaza Mz; M. Saiful Mujab; Satria Tenun Syahputra (Program studi Keagamaan Islam, 2023)
This article delves into the teachings of Islamic education found in Abdul Karim Amrullah's Tafsir Al-Burhan, specifically referencing QS. Al-'Alaq[96]: 1-5, which was published in 1927. The study was conducted using qualitative research methods and a content analysis approach. The results reveal five key teachings of Islamic education in QS. Al-'Alaq[96]: 1-5, including the importance of remembering Allah in all situations, abandoning pride and envy, teaching the Qur'an to those unfamiliar with the religion, emphasizing the value of literacy, and encouraging continuous learning. These teachings were not arbitrarily developed, but rather rooted in the history of education development in Minangkabau and Abdul Karim Amrullah's background as an educator and educational revolutionary of his time